Elderly individuals with increased risk of falls show postural balance impairment - Márcio Rogério de Oliveira (Fisioterapia em Movimento)
Introduction Falls are a serious public health problem. Objective The aim of this study was to evaluate whether elderly individuals with increased risk of falls have a postural balance deficit, evaluated using a force platform during a one-leg stance. Materials and methods The sample consisted of 94 physically independent elderly individuals from the EELO project. The instruments used were the Downton scale, in order to assess the risk as well as the history of falls, and the force platform to measure postural balance through parameters from the center of pressure (COP). Results Elderly individuals were split into two groups according to the score observed with the Downton scale: G1 — low fall risk (score ≤ 2) — and G2 — high fall risk (score > 2). No differences were observed between the groups concerning gender (P > 0.05, Chi Square test). On the other hand, individuals from G2 showed postural instability when compared to individuals from G1, and individuals from G2 showed higher values in all COP parameters analysed (Mann-Whitney test, P < 0.05). Conclusion It can be concluded that the Downton scale has sensitivity for identifying individuals with balance impairment as well as a risk of falls. Therefore, it may be suggested that this scale may be useful in primary health care for detecting falls in the elderly.